Knowledge Hoarding at a State University Library in Zimbabwe - Mutage, Moses; Dewah, Peterson (University of Dar es Salaam Library Journal, 2022)
Despite the need to bridge the knowledge gap introduced by technology, knowledge hoarding by library staff seems to affect service delivery at a state university library in Zimbabwe. The study employed a qualitative research approach in a case study design, informed by the interpretive paradigm. The target population of this study consisted of senior library management personnel and their subordinates. Maximal variation purposive sampling strategy was chosen to sample twenty-six library staff/ individuals that differ on some characteristics. Data were generated using interviews and observations. Key findings revealed that mistrust, unfair treatment, poor interpersonal relations, lack of recognition, and absence of a reward system induce knowledge hoarding and discourage library staff from sharing experiences. Furthermore, the study revealed that while librarians hoard knowledge as a security strategy for indispensability, hoarding knowledge has led to individualism and privatisation of knowledge. The study concluded that withholding of knowledge, for whatever reason, results in negative implications on the performance of new roles and service delivery. The study recommends that library staff should change from knowledge hoarding to sharing their knowledge; that the state library should implement a knowledge sharing policy; that the university library should reward knowledge sharing and recognize knowledge contributions from subordinates.